The life we bury [large type] : a novel - Eskens, Allen, 1963- (Wheeler Publishing, 2016)
College student Joe Talbert has an assignment to interview a stranger and write a brief biography. With deadlines looming, he heads to a nearby nursing home. Carl Iverson is a dying Vietnam veteran -- and a convicted murderer. Writing about him, Joe can't reconcile the heroism of the soldier with the despicable acts of the convict, and tries to uncover the truth.